Circuitos lúdicos para el desarrollo de la psicomotricidad de niños de 4 años - García Moran, Genesis Milena (2025)
Psychomotor development in 4-year-old children is important for their comprehensive development, as it encompasses motor, cognitive, and social skills. At the Juan E. Verdesoto Elementary School in Babahoyo, low psychomotor development was identified in children in sublevel II, evidenced by difficulties in carrying out activities such as running, jumping, maintaining balance, and manipulating small objects. These limitations affect their ability to fully participate in group activities, hinder their socialization, and generate frustration at not being able to perform tasks appropriate for their age. The research aimed to analyze the influence of play circuits on the development of psychomotor skills in 4-year-old children during the 2024-2025 school year. The methodology used was descriptive, with a non-experimental design and a qualitative approach, using techniques such as observations of 4-year-old children, interviews with the teacher and surveys with parents, with which the play circuits and their components and the psychomotor skills and deficiencies of the children were analyzed in detail, obtaining as a result the identification of the teacher's class dynamics and the level of psychomotor development of the children. It was concluded that the use of play circuits in the class contributes significantly to the psychomotor development of 4-year-old children at the Juan E. Verdesoto Basic Education School since they allow the stimulation of both gross and fine motor skills.